Preparation / Allocation / Habituation: The Holistic Approach to Migrant Exclusion - Xypolytas, Nikos (Social Cohesion and Development, 2018)
The article establishes a theoretical approach to migrant exclusion based on recent research and focuses on the importance of the experience and organization of work. The holistic approach recognizes three important stages in the process of exclusion: i) the preparation of future migrants in the country of origin through the integration and cultural acclimatization to casual and low-status work, ii) the allocation of migrant workers in low-status jobs in the host countries and iii) the habituation of migrant workers to the characteristics and demands of their work which leads to the reproduction of their social position.